قرآن میں مذکور عیسائی برادریوں کے تہذیبی اثرات: عصری تحقیقات کی روشنی میں ایک تجزیاتی مطالعہ: The Cultural Influence of Christian Communities Mentioned in the Qur’an: An Analytical Study in the Light of Contemporary Research - Muhammad Akram,; Dr. Abdul Ghaffar, (Al-Amīr Research Journal for Islamic Studies, 2025)
This study investigates the cultural influence of Christian communities mentioned in the Qur’an, placing their historical presence and interactions within the framework of modern scholarly research. By tracing early Christian groups such as the People of the Book, the followers of Prophet ʿĪsā (Jesus), and the communities addressed during the Prophet Muḥammad’s era the article highlights the Qur’anic depiction of their beliefs, ethics, and socio-cultural patterns. Contemporary research further clarifies how these communities functioned within the broader religious landscape of Late Antiquity and how their customs, institutions, and intellectual traditions shaped the region’s cultural fabric. In light of recent archaeological, historical, and textual studies, the article analyzes how Christian theological debates, monastic culture, educational systems, and literary heritage impacted shared cultural spaces in the Middle East. These findings show that the Qur’anic references to Christians were grounded not merely in theological discourse but also in real historical exchanges that reflected coexistence, debate, and mutual influence. The study underscores that Christian cultural systems ranging from moral teachings and social ethics to institutional structures played a notable role in shaping the intellectual environment in which early Muslim society emerged. Finally, the article examines the relevance of Christian cultural influences for contemporary Muslim societies. It argues that understanding the nuanced interaction between Muslims and Christians, as presented in the Qur’an and supported by modern research, can promote interreligious harmony, strengthen cultural literacy, and refine comparative civilizational studies. Such an approach allows modern scholarship to transcend polemical narratives and appreciate the depth of shared human experience among Abrahamic traditions. Keywords: Qur’anic Communities, Christians, Cultural Influence, Late Antiquity, Interreligious Relations.